The Graduation Requirements of High School Students from American Schools: Examining Graduation Requirements in American Schools in the United Arab Emirates – A Comparative Analysis of Multiple Case Studies - ELOSTA, JAILAN LOTFY (2022)
Purpose – Graduating from a high school is the steppingstone for the start of the future of the undergraduate study for any student that prepares for further postgraduate studies, workforce, and career paths. Every year, several new private schools open their doors for students to join. The Ministry of Education in a country sets the rules and regulations that need to be followed to ensure that the school is providing its students with the needed graduation requirements to join universities. The purpose of this study is to comparatively analyze the graduation requirements of various American schools in United Arab Emirates, examine their fulfilment of the graduation requirements as per the ADEK, KHDA, and MoE requirements, and finally propose suggestions/improvements for graduation requirements that better ensure the entry requirements for universities in UAE, as well as obtaining the UAE equivalency. Methodology – The study will adopt a comparative analysis of multiple case studies where the graduation requirements from different American schools in UAE will be examined and studied. The study will investigate the graduation requirements in four schools in Dubai, four schools in Abu Dhabi, four schools in the Northern Emirates, as well as the graduation requirements in four schools in the United States of America. The rationality of a comparative analysis stands on the examination of patterns of similarities and differences across conditions in the cases. The aim of this type of analysis is to identify conformations of causal conditions that are satisfactory for the existence of an outcome. Findings – The research examines the graduation requirements of different private American schools in the UAE – namely accreditation body, school rating, graduation credits, one credit calculations and the equivalency requirements. It has been revealed to the researcher that the sampled schools do not abide by the expectations of the MoE and its ministerial resolution, where students are graduating without fulfilling the graduation credits nor meeting the graduation requirements. Moreover, some schools include the word “American” in its name and assume to award the high school diploma, but they are not meeting the requirements of graduation. Implications – The research highlights the need for monitoring private schools, mainly the American schools, operating in the UAE to ensure meeting the graduation requirements and readiness of the students to be issued the UAE equivalency. Originality / Value - This study is part of numerous research studies that have been conducted to inform about the importance of fulfilling high school graduation requirements. There is a noticeable gap in research on the availability of data about local graduation policies. The study will provide a positive addition to the literature about graduation requirements from private American schools in the UAE while recommending policy improvement for graduation that will result in securing UAE equivalency requirements and students joining higher education. Consequently, the research can be used as a focal point for future disquisitions that addresses various other educational systems, other than the American schools, this includes, but is not limited to, the British system, the International Baccalaureate system, as well as the Indian system. With the availability of future information via the MoE’s official website, further statistical data can be collated to inform about the needed improvements to ensure securing the graduation of the students from any school system in the UAE.